Effects of fluoride and Aloe vera tooh gel in artificial white spot lesions in vitro - Silva, Tânia Mara Da; Fonseca, Beatriz Maria Da; Sales, Ana Luísa Leme Simões; Holleben, Priscila; Valera, Márcia Carneiro; AraÚjo, Maria Amélia Máximo De (Faculdade São Leopoldo Mandic, 2016)
ABSTRACTObjective: The aim of this study was to evaluate the effects of toothbrushing using a fluoride toothpaste and Aloe vera tooth gel on artificial white spot lesions through the Knoop microhardness (KHN) analysis.Methods: Sound bovine enamel samples (2 mm/diameter and 2 mm/depth) were prepared and immersed in artificial white spot lesion for 24 h. The preparation of artificial white spot lesions was performed by pH-cycling process. The samples were randomly divided into two groups (n=20), according the dentifrice used: containing fluoride (Colgate Total 12) or Aloe vera (Forever Bright Aloe Vera Toothgel). The top surface of samples was submitted to 10,000, 25,000, 50,000 and 100,000 brushing cycles (200 g load) in an automatic brushing machine with abrasive slurry. The KHN analysis were evaluated at baseline, after immersion in artificial white spot lesion and after 10,000, 25,000, 50,000 and 100,000 cycles of brushing. Data were analyzed by two-way repeated measures ANOVA and Tukey tests (p=0.05).Results: The KHN values significantly increased after brushing cycles compared to demineralized means. No significant differences showed for dentifrice factor (p=0.263). However, there were statistically significant differences between groups in cycles of brushing times (p=0.0001).Conclusion: The toothpastes (containing fluoride or Aloe vera) were effective in increasing the superficial microhardness of artificial white spot lesions.

RESUMOObjetivo:Avaliar o efeito da escovação simulada usando creme dental com flúor e Aloe vera em lesão de mancha branca artificial in vitro, através da análise da microdureza Knoop (KHN).Métodos:Amostras de esmalte bovino (2 mm/diâmetro e 2 mm/altura) foram preparados e imersos em solução artificial de cárie por 24 h. O preparo para indução de lesão de mancha branca foi realizado por processo de ciclagem de pH. As amostras foram aleatoriamente divididas em dois grupos (n=20), de acordo com o dentifrício utilizado: creme dental contendo flúor (Colgate Total 12) ou creme dental à base de Aloe vera (Forever Bright Aloe Vera Toothgel). A superfície das amostras foi submetida à 10.000, 25.000, 50.000 e 100.000 ciclos de escovação simulada (200 g/peso) em uma máquina de escovação. A análise de microdureza (KHN) foi realizada inicialmente, após o período de imersão em solução artificial de mancha branca e após 10.000, 25.000, 50.000 e 100.000 ciclos de escovação. Os dados foram submetidos aos testes RM-ANOVA dois fatores e Tukey (p=0.05).Resultados:Os valores de KHN aumentaram significantemente após os ciclos de escovação, quando comparado aos valores após a imersão em solução desmineralizante. Não houve diferenças estatisticamente significantes entre os cremes dentais (p=0.263). Entretanto, em relação aos ciclos de escovação, houve diferenças significantes (p=0001).Conclusão:Os cremes dentais (contendo flúor ou Aloe vera) foram efetivos no aumento da microdureza superficial em lesão artificial de mancha branca.
Efeito dos cremes dentais à base de flúor e Aloe vera na lesão artificial de mancha branca in vitro
Keywords: Aloe; Dental enamel; Toothpastes.; Aloe; Esmalte dentário; Creme dental.